1987
DOI: 10.1016/0266-7681(87)90076-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in open fractures of the distal phalanx?

Abstract: A prospective trial was undertaken on 85 adult patients with open fractures of the distal phalanges of less than 6 hours duration, treated by conventional surgery. They either received no antibiotic therapy, or cephradine in short or long courses. The infection rate was 30% in the group without antibiotics and less than 3% in the treated groups. Three different antibiotics regimes were compared, with no difference in the infection rate: therefore the simplest and surest method, a single pre-operative dose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…59 All current studies emphasize the need for thorough debridement of an open wound as the cornerstone of open fracture care and that certainly antibiotics are not a substitute for surgical debridement. 59,[73][74][75][76] As mentioned by Platt and Page, there is overwhelming evidence that antibiotics are required in a prophylactic and therapeutic role for dirty wounds. 23,30 -33 CARDIAC PATIENTS Shapiro has commented that it is unknown whether patients with prosthetic heart valves or mitral valve prolapse are at increased risk for development of endocarditis after clean hand surgery procedures.…”
Section: Complex Hand Traumamentioning
confidence: 97%
“…59 All current studies emphasize the need for thorough debridement of an open wound as the cornerstone of open fracture care and that certainly antibiotics are not a substitute for surgical debridement. 59,[73][74][75][76] As mentioned by Platt and Page, there is overwhelming evidence that antibiotics are required in a prophylactic and therapeutic role for dirty wounds. 23,30 -33 CARDIAC PATIENTS Shapiro has commented that it is unknown whether patients with prosthetic heart valves or mitral valve prolapse are at increased risk for development of endocarditis after clean hand surgery procedures.…”
Section: Complex Hand Traumamentioning
confidence: 97%
“…Sloan et al [9] found an infection rate of 30% in the group not given antibiotics compared with less than 3% in the treated group (cephradine). In this study, all patients were adults, and the infections were superficial.…”
Section: Discussionmentioning
confidence: 96%
“…Prophylactic antibiotic therapy is recommended by some authors for injuries of the distal phalanx with fractures [6,9]. Sloan et al [9] found an infection rate of 30% in the group not given antibiotics compared with less than 3% in the treated group (cephradine).…”
Section: Discussionmentioning
confidence: 98%
“…For the purpose of this analysis, only timing of the debridement was considered, regardless of where it was performed. Debridement within 6 hours of injury was clearly defined in 3 studies 1,3,18 (including 333 fractures) with an infection rate of 3.0% (10 fractures). Debridement within 12 hours of injury (1 study with 193 fractures) resulted in a 3.6% infection rate (Table 3).…”
Section: Effect Of Early Debridementmentioning
confidence: 99%
“…Two studies 7,13 (221 patients/24 infections) used antibiotics but did not specify the type or duration. Four studies 14,[18][19][20] (439 patients/28 infections), randomized administration of antibiotics, and clearly defined whether the infected patients had received antibiotics or not. For each of those studies, the odd ratios for developing an infection were calculated for patients who received antibiotics over those who did not.…”
Section: Effect Of Antibiotic Administrationmentioning
confidence: 99%